2022
DOI: 10.1021/acsapm.2c00840
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Derived Metal–Cysteine Coordination Complexes Crosslink Carboxylated Nitrile Rubber and Enable Room Temperature Self-Healing, Stretchability, and Recyclability

Abstract: In this study, we investigated a network of carboxylated nitrile rubber crosslinked by biologically derived coordination complexes that possesses good room temperature self-healing properties in addition to high tensile strength, stretchability, and recyclability. First, we showed the synthesis and analysis of coordination complexes composed of two metal salts (nickel nitrate and zinc nitrate), whose corresponding thiol and amino groups engage with the L-cysteine amino acid to produce the complex. Infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The metal–ligand coordination bonds into the rubber backbone give good strength to the rubber products as well as good self‐healing property to the polymeric material and recyclability 10 . Recently, this group has made a network in XNBR by incorporating a coordination complex of nickel nitrate and zinc nitrate with l ‐cysteine that showed self‐healing at room temperature along with very good stretchability, recyclability, and high tensile strength 11 . Utrera Barrios et al 12 reported XNBR composites, employing zinc oxide (ZnO), to form sufficient crosslinks through Zn 2+ /COO − interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal–ligand coordination bonds into the rubber backbone give good strength to the rubber products as well as good self‐healing property to the polymeric material and recyclability 10 . Recently, this group has made a network in XNBR by incorporating a coordination complex of nickel nitrate and zinc nitrate with l ‐cysteine that showed self‐healing at room temperature along with very good stretchability, recyclability, and high tensile strength 11 . Utrera Barrios et al 12 reported XNBR composites, employing zinc oxide (ZnO), to form sufficient crosslinks through Zn 2+ /COO − interaction.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, this group has made a network in XNBR by incorporating a coordination complex of nickel nitrate and zinc nitrate with L-cysteine that showed self-healing at room temperature along with very good stretchability, recyclability, and high tensile strength. 11 Utrera Barrios et al 12 reported XNBR composites, employing zinc oxide (ZnO), to form sufficient crosslinks through Zn 2+ /COO À interaction. Hafiz et al 13 described the crosslinking of XNBR with zinc thiolate, by creating reversible ionic bonding between XNBR chains.…”
mentioning
confidence: 99%
“…These polar groups might coordinate with Zn 2+ , displacing active water molecules. 52,53 This process helps inhibit side reactions and can also form ion channels to guide a Zn 2+ uniform deposition. 54,55 Additionally, pea protein is rich in glutamic acid, which can exist in the ionized form of glutamate.…”
Section: Resultsmentioning
confidence: 99%
“…The tensile properties are known to improve with increasing crosslink density until the critical crosslink density is attained. Beyond this limit, the tensile characteristics decline as a function of crosslink density, meaning that a crosslink density that is too high will inhibit energy dissipation through molecular mobility 54,55 . As a result, the slight decrease in tensile strength observed in N2BB, A2BB, and C5BB may be mostly attributable to the postcuring effect rise in crosslink density.…”
Section: Resultsmentioning
confidence: 99%